Preparation of nitrogen-doped biochar and its adsorption performance for Cr6+ and Pb2+ in aqueous systems - Zhang, Yazhai; Xia, Zhilei; Aainaa Izyan, Nafsun; Feng, Weiying (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Toxicity and pollution of heavy metals in water environments are very serious threats, and how to efficiently remove heavy metals is a difficult problem in water ecosystems. This study takes Cr and Pb as examples to study the adsorption effects of different types of modified biochar on these two heavy metals and their influencing mechanisms, with the aim of providing precise treatment schemes for water ecological health. Biochar was prepared from apricot branches, apricot shells, and corn stalks through nitrogen doping modification, and its structure and properties were characterized and analyzed. Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were employed to investigate the microstructure and surface chemical characteristics of the biochar. Adsorption experiments were conducted to evaluate its removal efficiency for Cr6+ and Pb2+ from aqueous solutions. The results showed that nitrogen-doped biochar prepared from corn stalks at 600 °C exhibited the highest Cr6+ adsorption rate of 81.09%, while the biochar prepared at 500 °C demonstrated the highest Pb2+ adsorption rate of 91.61%. Comparative analysis of FTIR and SEM data between nitrogen-doped biochar and its original counterparts revealed the underlying adsorption mechanisms, which involve a synergistic effect of coordination interaction, electrostatic attraction, and chemical reduction. This study highlights nitrogen-doped biochar as an efficient and cost-effective material for the removal of heavy metal ions from aqueous environments. It also provides theoretical and practical insights into the resource utilization of agricultural waste and the management of water pollution.